Nuevas prácticas curatoriales en los museos de San Luis Potosí. El Arte Contemporáneo visto desde plataformas virtuales - Jorge Arturo Mirabal Venegas; María Clara Ortega Guzmán (Les Cahiers ALHIM)
This paper addresses critical elements regarding contemporary art museums located in the city of San Luis Potosí, Mexico, in which the practices of curation of plastic and non-object works are applied in virtual media, which are evidencing the need to generate curatorial works carried out with greater professional and intellectual quality of a digital nature. The foregoing will be directly visible on the various virtual platforms currently offered, since this event marks a turning point in the Mexican artistic field. This problem calls into question the seriousness of carrying out curatorial practices within Mexican museums, since, at the time of publicizing emerging expressive currents and national artists with potential, they cause a certain critical impact or impression on the viewing public, the which does not come to have a broad opinion of this curatorial practice, but at the same time affects the artistic quality. The foregoing will be observed from the new curatorial practices that mark the reactivation of the museums of the capital of Potosí after the 2020-2021 health contingency, resuming the autumn celebration of Xantolo or Day of the Dead, one of the festivals with the greatest impact in the region and an event that marks a before and after in the new curatorial practices in that city.